Cystic lesions of pancreas: challenges in diagnosis and management - S Bohara (Society of Surgeons of Nepal, 2016)
Introduction: Pancreatic cysts are common (2.5%). Cystic neoplasms represent 10% of cystic lesions and 1% of pancreatic tumors. However, it is difficult to differentiate benign cyst from malignant cystic lesions preoperatively.